Defining Technology-Based Learning Media in Science Subjects for Elementary Schools - Firmansyah, Firmansyah; Tafakur, Tafakur; Destiana, Bonita; Dewi, Ayu Sandra (Jurnal Prima Edukasia, 2024)
Current learning media devices require an update by integrating information technology to support learning needs in the digital era 4.0. However, not all teachers can do it; soft and hard skills adapted to their field are needed. Based on this, researchers collaborated with automotive engineering and education science to analyze the need to develop learning media in elementary schools. The collaborative research employed qualitative methodology, incorporating interviews, analysis of documents, and open-ended questionnaires for data gathering. The analysis technique used is the Miles & Huberman, which consists of data condensation, data presentation, and conclusion. The results show that the development of technology-based media in simulators that can stimulate students' cognitive, affective, and psychomotor abilities in the classroom is needed. Furthermore, teachers can collaboratively conduct various activities, such as assembling, problem-solving, and creating something new through the media. The urgency of developing instructional media in elementary school for Science refers to the topics for which learning materials in Science kits are already available. However, underutilized use will not further stimulate students' creativity. Some important topics for media development include 1) changes in the state of matter, 2) energy and its changes, 3) the properties of conductors and insulators, and 4) electricity and magnet.